Self-Protection model through children's knowledge and assertive behavior as an early protection effort against sexual violence in Kubu Raya Regency - Sri Nugroho Jati; Vidyastuti (Insight: Jurnal Ilmiah Psikologi, 2024)
School-aged children are at risk of becoming victims of sexual abuse, highlighting the need for early self-protection programs. These programs should provide knowledge, training, and assertive actions as part of preventive psychoeducation for children. Studies show that between 20% and 33% of girls and 10% to 16% of boys will experience sexual abuse before reaching 18 years old. The Self-Protection Model aims to serve as an early protection program by equipping children with the knowledge to recognize and identify sexual abuse. This study employed a quasi-experimental method with a quantitative approach. The sampling method used was purposive sampling on 20 subjects consisting of male and female students who met the following criteria: aged 9-12 years and elementary school students. The measurement tools used were assertiveness scale and knowledge scale. The analysis using the non-parametric Wilcoxon test, demonstrated that the self-protection model significantly contributes to children's knowledge and assertive behavior in response to sexual violence. Efforts to prevent sexual violence should be directed at children, emphasizing the importance of providing knowledge and examples of assertive behavior. This study's findings indicated a significant improvement in children's knowledge and assertive behavior following the implementation of the Self Protection Model intervention, thereby empowering them to apply the newly acquired skills as a preventive strategy against sexual violence. Keyword: Self-Protection Model, Knowledge, Assertive Behavior, Sexual Violence.